An Empirical Study of the Relationship between Money Market Interest Rates and Stock Market Performance: Evidence from Zimbabwe (2009-2013) - Kganyago, Trust; Gumbo, Victor (International Journal of Economics and Financial Issues, 2015)
The research examines the long run relationship between money market interest rates and stock market returns in Zimbabwe from April 2009 to December 2013. The estimation model controls for Money supply growth rate, Inflation, Volume of Manufacturing Index, Crude Oil Price and Political Stability. All the variables were tested for unit root using ADF Test before Johansen cointegration tests. Based on VEC Granger Causality tests, findings show evidence of strong and statistically significant inverse causal relationship between money market interest and stock market returns. Findings also show existence of short run causality that runs from stock market returns to money market interest rates. This is believed to be caused by the passive nature of money market in Zimbabwe and non-functionality of RBZ in controlling interest rates through monetary policy. There is therefore need to implement robust and pragmatic macroeconomic policies like the repo market to reactivate the money market. Keywords: interest rates, stock market, ordinary least regression. JEL Classifications: C19, C22, C32, E43, E44, F59, G10